A within-subjects test of ego depletion and potential moderators. Issue 4 (2nd October 2022) - Calvillo, Dustin P.; Rodriguez, Katie; Nguyen, Theresa Ngan
Abstract: Ego depletion, the finding that initial exertion of self-control hinders performance on subsequent self-control tasks, has become a controversial topic. There have been discrepant results from empirical studies and different conclusions drawn from meta-analyses and multilab studies. We examined ego depletion and three potential moderators in a preregistered experiment using a within-subjects design in order to overcome limitations of the standard between-subjects design. In two sessions separated by 1 week, participants ( N = 214) completed an ego depletion or control version of a Stroop task. Each Stroop task was followed by manipulation check questions and an antisaccade task. Participants also completed measures of lay theory of willpower, trait self-control, and action orientation. There was no significant evidence for ego depletion, and Bayes factors strongly favored the null hypotheses that there was no difference in antisaccade performance (accuracy or response time) after ego depletion and control Stroop tasks. Additionally, lay theory willpower, trait self-control, and action orientation were not significantly related to ego depletion effects. Exploratory between-subjects comparisons that omitted participants who responded at lower than chance accuracy levels, however, found significant ego depletion effects. These results provide further evidence that ego depletion effects are elusive.